Функционирование гипертекста в среде конвергентных медиа: лингвистический анализ - Горошко, Елена Игоревна (Поволжская государственная социально-гуманитарная академия, 2011)
The paper enlightens the changes in linguistic hypertext research tools and methodology within convergent media computer-mediated communication (CMCMC) (Herring's Term 2011) initiated by shifts from web 1.0 and web 2.0 to web 3.0 conceptions. The author argues that the seeds of the future hypertext research can generally be discerned in the present, if anybody knows where to look.
Keywords: интернет-лингвистика; трансмедиа; гипермедиа; гипертекст